Simultaneous occurrence of extralobar pulmonary sequestration, esophageal duplication, and bronchogenic cysts in a Chinese child: a rare case report - Zhao, Huashan; Zhai, Yunpeng; Guo, Rui; Xu, Hongxiu; Huang, Sai; Lv, Longfei; Zhang, Shisong (Frontiers in Pediatrics, 2024)
The occurrence of simultaneous extralobar pulmonary sequestration, esophageal duplication, and bronchogenic cysts is relatively low. We report the case of a 9-month-old Chinese child who had a right lung cyst, detected in utero and was closely monitored until birth. At age 9 months, contrast-enhanced computed tomography revealed right mediastinal extralobar pulmonary sequestration and two cysts. The patient did not exhibit any abnormalities. However, the parents were concerned about the disease. Following positive psychological counseling to the parents, surgery was the strong desire. Subsequently, successful thoracoscopic surgery was performed, excising the three lesions. No postoperative complications occurred. Postoperative pathology confirmed extralobar pulmonary sequestration syndrome combined with esophageal duplication and bronchogenic cysts. The patient was followed-up at 1 and 12 months postoperatively and recovered well with no abnormal space occupation. In such cases, preoperative imaging examinations should be carefully performed, and intraoperative exploration should correspond to that before surgery to avoid lesion omission.